Optimasi Penjadwalan Pekerja Shift di Rumah Makan Cepat Saji (Fast Food Restaurant) menggunakan Algoritma Genetika (Studi Kasus: Warung Gunung di Kediri) - Ellita Nuryandhani Ananti; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Fast food restaurants are one of the businesses in the culinary field that are developing very rapidly at this time. Labor plays an important role in providing services to buyers where it can also affect income and also support the economy of a restaurant business, one of which is Warung Gunung (Wagu) in Kediri. In Wagu itself, there is a different division of job desc for each group of workers. When scheduling manually, it also takes a long time and is prone to human error. Therefore, it is necessary to have computerized scheduling of workers to carry out production activities and services to consumers effectively and efficiently. In this study, the scheduling process is carried out using the Genetic Algorithm method starting from the representation of chromosomes to the worker code and division, then carrying out a one-cut point crossover and reciprocal exchange mutation process to get new offspring which are then used in the selection process using elitism selection for the next generation. Based on the results of the parameter testing that has been carried out, it produces the most optimal solution without any violation of shift worker scheduling by producing the largest average fitness value is 1 which is found in the population size of 520, the number of generations is 450, and the combination of cr and mr is 0,6:0.4.